Pengembangan E-Modul Larutan Penyangga Berbasis Discovery Learning Untuk Kelas XI SMA/MA - Agil Aditya Dinata; Rahadian Zainul (Universitas Negeri Padang, 2020)
The purpose of this study is to produce a discovery learning based e-module on buffer solution topic for Class XI Senior High School (SMA/MA). The type of research used is Research and Development using 4-D models with 4 stages, namely: (1) define, (2) design, (3) develop and (4) disseminate. This e-module was validated by 2 Chemistry lecturer from FMIPA UNP and 3 Chemistry teachers at Pertiwi 1 Padang High School, while the practicality test was carried out by 2 chemistry teachers and 26 students of class XII MIA SMA Pertiwi 1 Padang. The validity and practicality data were analysed using the kappa cohen formula, the validity was 0.92 very high and the practicality of teachers and students was 0.94 and 0.83 very high. The data proves that the Buffer Solution e-module can be said to be valid and practical